2018
DOI: 10.4187/respcare.05471
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Mouthpieces on Impulse Oscillometry Results

Abstract: A circular mouthpiece coupled with a free-flow piece (B3) appeared to be the most suitable mouthpiece for the impulse oscillometry tests. It assured smaller impedance values for the respiratory system, and subjects expressed the most confidence in using this mouthpiece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
6
0
2
Order By: Relevance
“…5,17 Values of resonance frequency can be higher in the case of lung disorders, both restrictive and obstructive. 18,19 The area of reactance (AX) includes the area under the reactance curve from lowest frequency to Fres; increased values were correlated with distal obstruction.…”
Section: Parametersmentioning
confidence: 99%
“…5,17 Values of resonance frequency can be higher in the case of lung disorders, both restrictive and obstructive. 18,19 The area of reactance (AX) includes the area under the reactance curve from lowest frequency to Fres; increased values were correlated with distal obstruction.…”
Section: Parametersmentioning
confidence: 99%
“…Concerns have been raised about the low-impedance calibration devices used in some equipment despite methodological recommendations published long ago [5,6], which are far too small compared to the Z rs values encountered in clinical practice. Another concern relates to the simplistic correction for the filter-mouthpiece assembly, which does not take into account the shunt effect of the associated dead spaces on the measured Z rs [15,30].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous bacterial filters available for use with oscillometric systems, which will have a range of resistances. A single study showed differences in impedance measured with different filters by IOS in healthy adults [91]. A single study using the interrupter method in asthmatic children aged 4-16 years found a mean increase of 1.2 hPa•s•L −1 , but there was a wide variance of ±3.4 hPa•s•L −1 [92].…”
Section: System Resistance and Dead Spacementioning
confidence: 99%